DEBAT CAPRES CAWAPRES DALAM PERSPEKTIF SYARIAT ISLAM ( TINJAUAN ANALISIS SEMIOTIKA DEBAT CAPRES CAWAPRES PEMILU 2019) - A.Nur Aisyah Rusnali (fakultas Ushuluddin dan Dakwah IAIN Bone, 2019)
Abstract:The purpose of this study is to find out how the debate of the Capres andCawapres 2019, and to explore the view of Islamic Shari'a on the debates ofthe Capres and Cawapres 2019, is reviewed from a semiotic communicationstudy. The research method used is qualitative with a semioticcommunication approach. Semiotics is about the meaning of signs, markers,and signs. The debate in human life is a humane thing to happen. Because allmankind can't have the same thoughts. Depending on humans, the debateitself is. As is the case in determining the president's choice. Law in theability of debate or discussion, Islam has arranged it in such away. , Islamiclaw on the debate is not to do debate only for pleasure, it occurs in the debateprogram of 2019 candidate. The debate Program is carried out not forpleasure alone, but accompanied by a good purpose, namely to make thecommunity more familiar with the character of each candidate President andvice president, so that they easily determine the choice.Keywords: the candidate debate,Islamic Sharia, Semiotics.